THE IMPACT OF SHARIA FINTECH ON FINANCIAL LITERACY AND INCLUSION AMONG GENERATION Z IN INDONESIA: A TAM-BASED ANALYSIS - Silmy Nurvianty Juliana; Siti Ridha Farida; Yulistyne Kusumaningrum; An Bao Minh Phan (Universitas Muhammadiyah Prof DR HAMKA, 2026)
Research aims: This study aims to analyze the impact of Sharia fintech on financial literacy and financial inclusion among Generation Z in Indonesia, using the Technology Acceptance Model (TAM) as the underlying theoretical framework. Design/Methodology/Approach: This study adopts a quantitative explanatory approach. The population comprises Generation Z residing in West Java Province. Data were collected using purposive sampling techniques. A linear regression analysis was conducted using STATA version 17. Research findings: The results indicate that Sharia fintech has a positive and significant effect on both financial literacy and financial inclusion among Generation Z in Indonesia. These findings suggest that increased utilization of Sharia fintech contributes to improving financial understanding as well as access to financial services. Theoretical Contribution/Originality: This study provides empirical evidence that Sharia fintech makes a tangible and significant contribution to improving Generation Z’s ability to understand and manage personal finances. Moreover, Sharia fintech plays a positive role in facilitating access to financial products and services. Practitioners/Policy Implications: The findings in this study provide implications for Sharia fintech service providers to enhance their efforts in innovating, particularly by offering educational features integrated with Sharia values. Research Limitations/Implications: This research is still limited to the population scope in West Java province, thus requiring further studies to obtain more representative results with a broader geographical scope.